The Effect of Budget Participation, Budget Emphasis, and Compensation on Budget Slack at Le Grande Bali - Anak Agung Istri Indah Utari Dewi; I M A Putrayasa; A A G M Suarjana (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
Managers and supervisors at Le Grande Bali participate in preparing company budgets and pressured to be able to achieve budget targets, so managers and supervisors make it easier to achieve budget targets through budgetary slack to get compensation in the form of bonuses but also offset by penalties to managers and supervisors and all existing employees at Le Grande Bali a truth inducing system. This study aims to determine the effect of budget participation, budget emphasis, and compensation on budgetary slack both partially and simultaneously on Le Grande Bali. The type of data used in this study is primary data obtained by distributing questionnaires to respondents. The questionnaire was distributed to the Head of Department and supervisors of each section department and subordinates who were involved in the budgeting process at Le Grande Bali. The sampling method in this study uses saturated samples using multiple linear regression analysis techniques. The results of this study indicate that: (1) Budget participation does not affect budgetary slack. (2) Budget emphasis has a significant positive effect on budgetary slack. (3) Compensation has no effect on budgetary slack. (4) Budget participation, budget emphasis, and compensation simultaneously have a significant positive effect on budgetary slack.